Residual Stress Effects in Fatigue 1982
DOI: 10.1520/stp30099s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tensile Residual Stresses on the Fatigue Behavior of Welded Joints in Steel

Abstract: Fatigue tests were carried out on fillet welded joints in four steels, with yield strengths ranging from 332 to 727 N/mm2, under various applied load ratios. Some specimens were stress-relieved but most were spot-heated to ensure that high tensile residual stresses, as would be present in as-welded joints in real structures, were present in the specimens. The aim was to investigate the effect of tensile residual stresses on the fatigue behavior of fillet welded joints under different load ratios and the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…7 Previous work 14,23 has shown that when equation (4) is applied without taking into account the short crack effects, fatigue limits and fatigue strength at low stress levels are overestimated. However, the overestimation was attributed to incomplete stress relief and the influence of short crack behaviour was not taken into account.…”
Section: Implications Of Short Crack Regimementioning
confidence: 99%
“…7 Previous work 14,23 has shown that when equation (4) is applied without taking into account the short crack effects, fatigue limits and fatigue strength at low stress levels are overestimated. However, the overestimation was attributed to incomplete stress relief and the influence of short crack behaviour was not taken into account.…”
Section: Implications Of Short Crack Regimementioning
confidence: 99%
“…The first clearcut result is that at higher loads, the fatigue life is not influenced by the longitudinal and transversal residual stresses, both compressive and tensile. This is because the cyclic external load, overimposed to the pre-existing stress, is sufficiently high to yield the material and to partially relax the residual stress, as confirmed by several authors [35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 81%
“…The heat source, which was originally described for plate welding [22,23], is modified in order to make it appropriate for circumferential girth welding. Equations (2) and (3) represent the cylindrical form of this equation [24].…”
Section: Heat Source Modellingmentioning
confidence: 99%
“…These distortions can lead to poor sealing performance of the joint. In addition, it is important for the function of a structure that the welding residual stress field should be known quantitatively, as it may influence the mechanical behaviour of structures including fracture, stress corrosion cracking, fatigue, and buckling [2]. Tensile residual stresses are detrimental to the initiation and growth of fatigue cracks.…”
Section: Introductionmentioning
confidence: 99%